Development and refinement of a communication guide to help young adults in Texas reconnect and reduce loneliness - Erin E. Donovan; Audrey Shaffer; Emily Kaiser; Karly Quaack; Michael Mackert; Weijia Shi; Daniela De Luca (PEC Innovation, 2024)
Objective: Loneliness among young people is a contemporary public health crisis exacerbated by the COVID-19 pandemic. The present research examined the development of a modest yet meaningful health communication intervention resource that would become an asset in a larger health campaign: a communication guide aimed at helping young people reach out and reconnect with others. Methods: Study One established the need for a loneliness intervention in Texas with survey data (N = 795). A communication guide was developed based on research and theory. Study Two employed focus group interviews with potential audience members (N = 31) to critically assess and inform revisions to the communication guide. Results: Study One results indicated that a substantial proportion of young adult Texans felt as though their social connection had decreased and their loneliness had increased since the onset of the pandemic. Themes in focus group responses from Study Two suggested several strengths of the communication guide and some opportunities for revision. Conclusion: A communication guide with tips for reconnecting could be a valuable tool to empower young people and promote social connection. Innovation: This study involved the development and refinement of a new communication resource that was informed by a priority audience of a major health communication campaign.